Food geographies I: Relational foodscapes and the busy-ness of being more-than-food. (April 2016) - Goodman, Michael K.
The study of foodscapes has spread throughout geography at the same time as food scholarship has spearheaded post-disciplinary research. This report argues that geographers have taken to post-disciplinarity to explore the ways that food is 'more-than-food' through analyses of the visceral nature of eating and politics and the vital (re)materializations of food's cultural geographies. Visceral food geographies illuminate what I call the 'contingent relationalities' of food in the critical evaluation of the indeterminate, situated politics of 'feeling food' and those of the embodied collectivities of obesity. Questions remain, however, about how a visceral framework might be deployed for broader critiques within foodscapes and the study of human geography. The study of food's vital materialisms opens up investigation into the practices of the 'makings' of meat, food waste and eating networks. Analysis of affect, embodiment and cultural practices is central to these theorizations and suggests consideration of the multiple materialisms of food, space and eating. There is, I contend, in the more radical, 'post-relational' approaches to food, the need for a note of caution. Exuberant claims for the ontological, vital agency of food should be tempered by, or at least run parallel to, critical questions of the real politik of political and practical agency in light of recent struggles over austerity, food poverty and food justice.